Solid-State Transformer for Power Distribution Grid Based on a Hybrid Switched-Capacitor LLC-SRC Converter: Analysis, Design, and Experimentation - Rogerio Luiz Da Silva; Victor Luiz Flor Borges; Carlos Eduardo Possamai; Ivo Barbi (IEEE Access, 2020)
A solid-state transformer (SST) is being proposed for a distribution grid of 13.8 kV/380 V. The SST is based on the input-series output-parallel (ISOP) arrangement of twelve modules using the 1.2 kV SiC switches. The cost and losses analysis are discussed through a case study regarding the number of modules using the 1.2 kV and 1.7 kV SiC switches. The modules are composed of two stages: the first one is an AC-|AC| low-frequency rectifier and the second one is an |AC|-|AC| medium frequency Hybrid Switched-Capacitor LLC Series-Resonant Converter (HSCSRC). A single back-end |AC|-AC low-frequency inverter is employed to generate the low voltage AC output port of the SST. The switched capacitor ladder cell in the HSCSRC converter enables the reduction of the number of modules employed on the ISOP arrangement because the voltage stresses on the MV side's switches are halved, while the resonant stage increases the efficiency of the structure due to soft-switching on all the switches. Moreover, the front-end AC-|AC| and back-end |AC|-AC low-frequency converters enable the use of two-quadrant switches on the |AC|-|AC| HSCSRC converter, reducing the switch count on the medium frequency stage. The operating behavior and design methodology of the SST's modules are presented. A single module reduced scale prototype with the rated power of 1.67 kVA and an input voltage of 1.15 kV and an output voltage of 220 V is experimentally verified. The maximum efficiency is 97%.